CARCASS AND ORGAN CHARACTERISTICS OF ROSS 308 BROILER CHICKENS FED BLACK SOLDIER FLY LARVAE MEAL - Ilaboya, I. I.; Abdulazeez, R. O.; Edafewhara, S. E.; Imouokhome, J. I.; Oyedeji, J. O. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study investigated the effect of feeding black soldier fly larvae meal (BSFLM) as a substitute for soybean meal (SBM) in broiler finisher diets on the carcass and organ characteristics of Ross 308 broiler chickens. A total of 120 broiler chicks were randomly assigned to five treatments with eight birds per replicate. The BSFLM was incorporated into the diets at 0% (control, T1), 25% (T2), 50% (T3), 75% (T4) and 100% (T5) on a protein basis. The birds were subdivided into three replicates of eight birds each in a Completely Randomized Design arrangement. At the end of eight weeks feeding trial, 2 birds per replicate were randomly selected according to average group weight and slaughtered for carcass and organ evaluation. The results demonstrated that carcass yield parameters, including breast, drumstick, thigh, and back weights, were significantly improved (P<0.05) in birds fed BSFLM. The wing weights were significantly (P<0.05) higher in T2 and T4 when compared with the 100% inclusion level. The shank weights were not significantly different (P>0.05) within all the treatment means. The large intestine was significantly (P<0.05) influenced when birds were fed diets with T2 and T4. The weight of the gizzard was similar across all treatments except for T5. It was observed that birds fed BSFLM diets elicited better cut part weights. Therefore, black soldier fly larvae meal improved carcass and organ characteristics of ROSS 308 broiler finishers without any adverse effect and 75% inclusion gave an optimum performance on carcass and organ traits.